Psychological intervention in the treatment of ADHD in adults: a systematic review - Tapullima Mori, Calixto (2024)
In the last years, many treatments for ADHD in adults have been developed, such as multimodal, pharmacological, mixed and even neurological; however, these have adverse effects which increase treatment abandonment. The objective of the present systematic review was to identify the effects of psychological interventions in order to decrease ADHD symptoms in adults. For this, it was carried out a search in Scopus, Web of Science and Pubmed databases. In this study randomized controlled trials and experimental studies with control group were included. We identified six documents, which reported cognitive-behavioral, mindfulness and automatic alert treatments. Participants were 18 to 65 years old and 77% were women. In some cases, treatment groups shown improvements in attention and decreased hyperactivity-impulsivity symptoms. Cognitive behavioral therapy interventions, although not directed toward symptom mitigation, along with mindfulness and automatic alertness training therapy are effective in reducing ADHD in adults; however, the studies reviewed have not evaluated the sustainability of long-term outcomes